Severe Complicated Plasmodium Vivax Malaria Presenting as Shock in a Child - Veeranna Kotrashetti; Vijay Baburao Sonawane; Kapil S Bainade; Revanth Sai Madhav (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Malaria is a vector-borne disease caused by a Plasmodium parasite having five species (falciparum, vivax, ovale, malariae and knowlesi) trans- mitted to humans through the bite of an infected Anopheles mosquito. South East Asia is the second most affected region in the world, with India carrying the highest burden of the disease. Plasmodium vivax and Plasmodium falciparum are the most common species found in India. Severe complications of malaria have been more commonly seen in Plasmodium falciparum infections, and those caused by Plasmodium vivax have been considered benign. But in recent times, the severity caused by Plasmodium vivax has been emerging in India and is in equal ratio with Plasmodium falciparum to the malaria incidence. Here we report a case of a 5-year-old boy who presented with high-grade fever with chills, burning micturition, weak peripheral pulses, reduced oral acceptance, hypotension and pallor. The diagnosis was established by a thick and thin film of peripheral blood smear examination under oil immersion with Giemsa stain and Malarial Antigen Test. The child was started on anti-malarial therapy and fluid therapy was given to treat shock.